Evaluation of metal powder forming parameters at above ambient temperature - Rahman M.M.; Nor S.S.M.; Saktisahdan T.J.; Rahman H.Y. (2023)
This paper presents the results of an experimental investigation to evaluate the forming parameters for the compaction of iron powder ASC100.29 at above ambient temperature. A lab-scale uniaxial die compaction rig was designed and fabricated which enabled the generation of green samples from the stated powder mixed with lubricant at different forming parameters. The characterization of green samples was conducted through the measurements of density, hardness, and bending strength whereas the microstructures were observed through Scanning Electron Microscopy (SEM). The results revealed that defect-free yet high density and stronger green compacts could be generated by adding 0.6 wt% zinc stearate, mixing for 30 minutes, and compacting the powder mass at 180C. The suitable compaction load is found to be 125 kN.